Ear Aesthetics: Investigation by the Use of an Online Viral Survey. Issue 3 (March 2017) - Steele, Jessica; Farmer, Eleanor; O'Hara, Justine; Bulstrode, Neil
Abstract : Introduction: The ear is a key facial feature and yet few studies have previously assessed ear aesthetics. This study aimed to assess the anatomical components of the ear that have the greatest impact on the perception of ear aesthetics. Materials and Methods: Three photographs of a male adult ear (close-up, lateral, posterior) were digitally manipulated such that in each, 1 anatomical element of the ear was either enlarged or reduced. A complete set of 16 photographs including a repeat of the original ear as a control were randomized and entered into an online survey that required respondents to rate the attractiveness of each ear on a scale of 1 (least attractive) to 10 (most attractive). The survey was disseminated using email and social media. Results: A total of 248 responses were received, 155 women and 92 men. Respondents were grouped by demographics of age and occupation. Reducing (R) or enlarging (E) the helix (R, P = 0.0256; E, P = 0.003), concha (R, P = 0.0002; E, P = <0.0001) and lobule (R, P = 0.0006; E, P < 0.0001) had a significant effect on ratings of attractiveness. Altering the tragus had no significant effect (R, P = 0.448; E, P = 0.201). In lateral view, raising the height of the ear had a significant effect ( P = <0.0001) but not in lowering the height ( P = 0.3038). Increasing and decreasing the projection of the ears both had a significant effect ( P < 0.0001). Conclusions: The results of this study have provided useful evidence regarding the anatomical components of the ear that have the greatest effect on ear aesthetics. Furthermore, this study has proven the usefulness of conducting research using viral online surveys.